2022
DOI: 10.3390/su142215093
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Effect of Financial Literacy and the Moderating Role of Social Capital in the Relationship between Financial Inclusion and Sustainable Development in Cameroon

Abstract: Financial inclusion has a wide range of positive effects on sustainable development, but studies indicate a lack of awareness about financial services in the large group of financially excluded individuals within the economy. This paper examines the mediating effects of financial literacy and the moderating role of social capital on the relationship between financial inclusion and sustainable development in Cameroon. A PLS-SEM model was used with 488 collected samples as empirical data from the residents of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 124 publications
(190 reference statements)
1
3
0
Order By: Relevance
“…Yang et al [ 1 ] also observed a comparable outcome, affirming that RE decreases the quantity of carbon emissions in China. These results additionally corroborate the findings of [ 81 ], who achieved comparable results in nations with high-income, upper-middle income, and low-income. Developing nations have escalated their use of renewable energy (RE), a sustainable energy source that aids in the reduction of CO 2 emissions.…”
Section: Resultssupporting
confidence: 91%
“…Yang et al [ 1 ] also observed a comparable outcome, affirming that RE decreases the quantity of carbon emissions in China. These results additionally corroborate the findings of [ 81 ], who achieved comparable results in nations with high-income, upper-middle income, and low-income. Developing nations have escalated their use of renewable energy (RE), a sustainable energy source that aids in the reduction of CO 2 emissions.…”
Section: Resultssupporting
confidence: 91%
“…As women are financially empowered, which augments the financial prominence of women within both familial and societal spheres trust between village women and nongovernmental organizations (NGOs), this has streamlined access to microfinance institutions and loans. This economic gain from minimizing the crop losses of extreme natural events and microfinance institutions is termed as financial capital [33].…”
Section: Financial Capitalmentioning
confidence: 99%
“…This research also aspires to present a globally applicable framework that could potentially influence cocoa production dynamics in similar regional contexts across the world. By filling this critical research void, this study aims to contribute significantly to the sustainable development of cocoa-producing communities (Abdullahi et al, 2022;Lontchi et al, 2022) and fortify the resilience of the global cocoa supply chain (Fountain and Hütz-Adams, 2020).…”
Section: Introductionmentioning
confidence: 99%